Facile Characterization of the Immobilization of Streptavidin on Magnetic Submicron Particles with a Fluorescent Probe of Streptavidin. Issue 6 (June 2013) - Long, Gaobo; Zhang, Yi; Yang, Xiaolan; Pu, Jun; Qin, Jialin; Liu, Lin; Liao, Fei
To characterize streptavidin immobilization on magnetic submicron particles (MSPs), residual streptavidin after magnetic removal of immobilized streptavidin was quantified with N -biotinyl- N ′-(1-naphthyl)-ethylenediamine (BNEDA) based on Forster resonance energy transfer. Residual BNEDA after magnetic removal of bound BNEDA was measured by its own fluorescence. Streptavidin was immobilized at about 12 mg per gram of MSPs and easily retained over 50% of its original activity. These assays facilitated optimized streptavidin immobilization on MSPs.